2015
DOI: 10.1051/ocl/2015011
|View full text |Cite
|
Sign up to set email alerts
|

Erucic acid rapeseed: 1. Prospects of improvements

Abstract: -In the current context of boosting production of high erucic acid rapeseed, because of the wide range of its industrial applications, this literature review is designed to provide a general overview of available varieties, current knowledge of plant improvement and paths of developing research to increase competitiveness of varieties with high erucic acid content. A limited market dominated by a few companies, cropping burdens of high erucic acid rapeseed varieties among the majority "00" varieties and the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…At the beginning of the era of rape modification, erucic acid occurred extensively in seed oils of the mustard family ( Cruciferae ) and distinguished these from most other vegetable oils which generally contain fatty acids with 16 and 18 carbon atoms . Erucic acid ( cis ‐13‐docosenoic acid, C22:1) is a long chain monounsaturated fatty acid with 22 carbon atoms, with a double bound at the cis‐13 position of the carbon chain . It is built‐in the TAG molecules.…”
Section: Reduction In Antinutritive Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the beginning of the era of rape modification, erucic acid occurred extensively in seed oils of the mustard family ( Cruciferae ) and distinguished these from most other vegetable oils which generally contain fatty acids with 16 and 18 carbon atoms . Erucic acid ( cis ‐13‐docosenoic acid, C22:1) is a long chain monounsaturated fatty acid with 22 carbon atoms, with a double bound at the cis‐13 position of the carbon chain . It is built‐in the TAG molecules.…”
Section: Reduction In Antinutritive Compoundsmentioning
confidence: 99%
“…The enzyme acyl‐CoA elongase, which is responsible for erucic acid biosynthesis, is situated in the endoplasmic reticulum. The elongation stage studied in Lunaria annua includes the following steps: condensation of oleoyl‐CoA and malonyl‐CoA and creation of 3‐ketoacyl‐CoA; reduction of 3‐ketoacyl CoA to 3‐hydroxyacyl‐CoA; dehydration of 3‐hydroxyacyl‐CoA and 2,3 transenoyl‐CoA reduction …”
Section: Reduction In Antinutritive Compoundsmentioning
confidence: 99%
“…Erucic acid (cis-13-docosenoic acid, C22:1) is a straight-chained mono-unsaturated very-long-chain fatty acid (VLCFA) with 22 carbon atoms and a double bond at the cis-13 position of the carbon chain. Biosynthesis of this fatty acid involves chain elongation of oleic acid (cis-9-octadecenoic acid, C18:1) to gondoic acid (cis-11-eicosenoic acid, C20:1) and then to C22:1 (Sanyal et al 2015). This reaction is catalyzed by ß-ketoacyl-CoA synthase (KCS), a membrane-bound enzyme that utilizes malonyl-CoA as the source of the two carbon atoms added in each cycle (Griffiths et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to low-erucic Brassica oils, high erucic oils have a higher energy potential (Semenov et al 2006) and are more desirable substrates for biodiesel (Vicente et al 2005) and biofuel (Zhao et al 2016) production. High erucic acid rapeseed (HEAR), currently the main feedstock for erucic acid used in industrial applications, contains about 50% of this fatty acid (Sanyal et al 2015). For improved technical utility and enhanced marketability of carinata oil, it is desirable to increase the C22:1 content and to simultaneously decrease the content of C20:1, polyunsaturated fatty acids (PUFA,linoleic [C18:2] and linolenic [C18:3] acids) and saturated fatty acids (palmitic [C16:0] and stearic [C18:0] acids).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al,(2016) reported that enhancing palmitic acid on cotton seed might be done through improvement of gh KAS II enzymeto catalyse palmitoyl ACP. Both loci were known to affect production of palmitic acid in various plants(Fourmann et al, 1998;Roscoe et al, 2001;Yan et al, 2015;Sanyal et al, 2015).…”
mentioning
confidence: 99%